Clinical Relevance of HLA Antibody Monitoring after Kidney Transplantation - Christian Morath; Gerhard Opelz; Martin Zeier; Caner Süsal (Journal of Immunology Research)
In kidney transplantation, antibody-mediated allograft injury caused by donor HLA-specific antibodies (DSA) has recently been identified as one of the major causes of late graft loss. This paper gives a brief overview on the impact of DSA development on graft outcome in organ transplantation with a focus on risk factors for de novo alloantibody induction and recently published guidelines for monitoring of DSA during the posttransplant phase.